The Swedish budget: 1979/80 - Sweden; Sweden (Stockholm, Ministry of Economic Affairs., 1979)
A summary of economic policy in 1977 and 78. It covers goals, directions, distributions, industrial, employment, fiscal and credit policy.
"A summary."
SERBIB/SERLOC merged record; sju 25/01/2019
Loans
Keywords: Budget; Budget; Economic history; Sweden; Sweden